2017
DOI: 10.1007/s10973-017-6471-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-rheological properties of coal-tar pitch modified with phenol-formaldehyde resin

Abstract: Test results of changing the thermo-rheological properties of coal-tar pitch under influence of phenolformaldehyde resin are presented in this research work. Influence of modifying agent amount and crosslinking conditions (time) of resin in bitumen was evaluated. Tests were carried out using the rheometer in oscillation mode. They enabled the evaluation of changes in bitumen viscous and elastic properties and draw the conclusions about changes in bitumen structure on that basis. Compositions of the coal-tar pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A pragmatic approach could be to blend bio-derived and fossil-derived binders, for example, blending coal tar pitch and biomass pitch [54] or phenolic resins [112].…”
Section: Mixed Bindersmentioning
confidence: 99%
“…A pragmatic approach could be to blend bio-derived and fossil-derived binders, for example, blending coal tar pitch and biomass pitch [54] or phenolic resins [112].…”
Section: Mixed Bindersmentioning
confidence: 99%
“…This is an obvious drawback which needs to be overcome when these resins used. [59] PF (phenol-formaldehyde) resins and their reinforced materials can also resist harsh thermal conditions, they can be used as carbon-mineral materials by blending with other substances and they also have other applications [60][61][62] ; however, researchers should also consider their adhesive and toughness properties during applications.…”
Section: Farid Bakir Is Professor At Arts Et Métiers Paristech Andmentioning
confidence: 99%
“…At the Institute of Chemistry, Warsaw University of Technology in Plock, have been being carried out studies on bitumen-polymeric materials for several years. They are aimed at the improvement of utility properties of coaloriginated bitumen and utilization of waste polymers [17][18][19][20]. It was demonstrated that pitch-polymer compositions can be used for the preparation of carbon adsorbents [21][22][23] and mineral-carbon adsorbents [24,25].…”
Section: Introductionmentioning
confidence: 99%